2022
DOI: 10.1039/d2mo00107a
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of long non-coding RNA-based biomarkers in the urinary sediment and urinary exosomes for non-invasive diagnosis of bladder cancer

Abstract: Bladder cancer (BC) frequently causes a heavy disease burden for patients because of its easy recurrence. There is still lack of convenient and effective methods to diagnose or monitor BC...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, exosomal multiple-lncRNA assays generated a pooled AUC of 0.87, while single ones gave rise to a pooled AUC of 0.82, which demonstrated the superiority of exploiting panels of exosomal ncRNAs to get a full picture. As depicted in Table 1 , exosomal lnc-MALAT1, PCAT-1, and SPRY4-IT1 from urine [ 6 ]; exosomal lnc-UCA1-201, UCA1-203, MALAT1, and LINC00355 from urine [ 8 ]; exosomal lnc-PCAT-1, UBC1, and SNHG16 from serum [ 10 ]; exosomal lnc-MIR205HG and GAS5 from urine [ 12 ]; exosomal miR-96-5p and miR-183-5p from urine [ 15 ]; exosomal miR-93-5p and miR-516a-5p from urine [ 16 ]; and exosomal lnc-RMRP, UCA1, and MALAT1 from urine [ 18 ] all manifested satisfying diagnostic value for bladder cancer. The potential molecular mechanism about the limitation of exosomal single-ncRNA biomarker maybe that aberrant levels of single ncRNA might be related to various types of cancers [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, exosomal multiple-lncRNA assays generated a pooled AUC of 0.87, while single ones gave rise to a pooled AUC of 0.82, which demonstrated the superiority of exploiting panels of exosomal ncRNAs to get a full picture. As depicted in Table 1 , exosomal lnc-MALAT1, PCAT-1, and SPRY4-IT1 from urine [ 6 ]; exosomal lnc-UCA1-201, UCA1-203, MALAT1, and LINC00355 from urine [ 8 ]; exosomal lnc-PCAT-1, UBC1, and SNHG16 from serum [ 10 ]; exosomal lnc-MIR205HG and GAS5 from urine [ 12 ]; exosomal miR-96-5p and miR-183-5p from urine [ 15 ]; exosomal miR-93-5p and miR-516a-5p from urine [ 16 ]; and exosomal lnc-RMRP, UCA1, and MALAT1 from urine [ 18 ] all manifested satisfying diagnostic value for bladder cancer. The potential molecular mechanism about the limitation of exosomal single-ncRNA biomarker maybe that aberrant levels of single ncRNA might be related to various types of cancers [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The studies over the past 10 years share some common exosomal contents including MALAT1, PCAT-1 and PTENP1. Many studies have demonstrated that these three molecules play key roles in bladder cancer and can be used as accurate biomarker for bladder cancer [ 113 , 127 , 129 , 132 , 133 ]. The phosphatase and tensin homologue (PTEN) is an essential tumor suppressor [ 138 ].…”
Section: Discussionmentioning
confidence: 99%
“…a2M (alpha-2-macroglobulin) has been reported to be upregulated in the urine exosomes of bladder cancer patients [ 112 ]. Moreover, a three exosomal lncRNA panel (RMRP, UCA1 and MALAT1) are elevated in bladder cancer, and is correlated with the tumor stage of bladder cancer [ 113 ]. Furthermore, the exosomal proteins derived from bladder cancer urine and healthy controls are significantly different, indicating their potential as a noninvasive biomarker [ 114 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…70 With 80.0% sensitivity and 81.4% specificity, the urine exosomal RMRP, UCA1, and MALAT1 lncRNA panel is a potential biomarker for the diagnosis of breast cancer based on The Cancer Genome Atlas (TCGA) database or literature review. 71 With an AUC value of 0.7813, UCA1 was released into exosomes and present in the serum of patients with pancreatic cancer at a significantly higher level than healthy controls. Therefore, UCA1 may be useful as an early biomarker against cancer.…”
Section: Lncrnas As Cancer Biomarkersmentioning
confidence: 94%